2017
DOI: 10.1016/j.celrep.2017.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Global Hypertranscription in the Mouse Embryonic Germline

Abstract: Summary Primordial germ cells (PGCs) are vital for inheritance and evolution. Their transcriptional program has been extensively studied and is assumed to be well-known. We report here a remarkable global upregulation of the transcriptome of mouse PGCs compared to somatic cells. Using cell-number normalized genome-wide analyses, we uncover significant transcriptional amplification in PGCs, including mRNAs, rRNA and transposable elements. Hypertranscription preserves tissue-specific gene expression patterns, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 41 publications
5
66
1
Order By: Relevance
“…We observed that a slow RNAPII mutant caused embryonic lethality even in heterozygosity (Fig 2). There is evidence that the transcriptional output is crucial in specific developmental stages associated with stem cell expansion, as evidenced by their hypertranscription states (Koh et al, 2015;Percharde et al, 2017). It is possible that a slow elongation rate cannot sustain the high levels of mRNA production required at early stages of development.…”
Section: A Slow Elongation Rate Causes Early Embryonic Lethalitymentioning
confidence: 99%
“…We observed that a slow RNAPII mutant caused embryonic lethality even in heterozygosity (Fig 2). There is evidence that the transcriptional output is crucial in specific developmental stages associated with stem cell expansion, as evidenced by their hypertranscription states (Koh et al, 2015;Percharde et al, 2017). It is possible that a slow elongation rate cannot sustain the high levels of mRNA production required at early stages of development.…”
Section: A Slow Elongation Rate Causes Early Embryonic Lethalitymentioning
confidence: 99%
“…Ezhip's pattern of expression is distinct from that of Ezh2, which is expressed tissue-wide, with the strongest expression observed in spleen. Analysis of public gene expression datasets from fetal gonads 36 indicates Ezhip is preferentially expressed in E13.5 primordial germ cells (PGCs) compared to somatic cells, correlating with germ cell markers such as Piwil2 or Prdm14 (Supplementary Figure 1G). Interestingly, Ezhip belongs to a set of genes referred to as "germlinereprogramming-responsive" that become active following PGC DNA demethylation 37 , as they are associated with strong CpG island promoters.…”
Section: Identification Of a New Cofactor Of Prc2 In The Gonadmentioning
confidence: 99%
“…First, global changes in transcriptional output are not captured by standard RNA‐seq methods. For example, we recently used cell‐number normalized RNA‐seq to document that the mouse embryonic germline is in a state of global hypertranscription, including at TEs . Second, a high proportion of LINE1 RNA is chromatin associated, and this fraction tends to be resistant to standard extraction of total cellular RNA .…”
Section: Conclusion and Looking Ahead: Line1 As Dual Regulator Of Gementioning
confidence: 99%
“…[79] TEs such as LINE1 and various ERVs become globally demethylated and expressed during the major waves of epigenetic erasure that take place during preimplantation and germline development (Figure 1). [80][81][82][83][84][85] Similarly, a relaxation of H3K9me2-based repression of TEs occurs in PGCs, contributing to their derepression. [86][87][88] As described above, many TE families act as important cis-elements for gene regulation.…”
Section: Emerging Evidence For Essential Roles For Expressed Tes Durimentioning
confidence: 99%
See 1 more Smart Citation